Effects of Light Stimulus Frequency on Phase Characteristics of Brain Waves - Nishifuji, S.; Fujisaki, K.; Tanaka, S. (SICE Annual Conference 2007, 2007)
Dependence of phase response of electroencephalogram (EEG) on stimulus light frequency is investigated under the condition of the stimulus frequency in the range from 5 to 20 Hz for clarifying the effect of the entrained alpha wave to the response of the EEG. Under the flicker stimuli the frequency of which is less than 8 Hz, the response of EEG to the stimuli is rather disordered; the phase of the EEG synchronized to the stimuli (steady-state visually evoked potential, SSVEP) complicatedly fluctuates with time. However, under the condition that the stimulus frequency is in the range of the alpha wave (8-13 Hz), the phase of the SSVEP is considerably stabilized. The phase of the SSVEP forms the anti-phase relationship between the occipital and frontal lobes. The spatial phase structure of the SSVEP for a half of subjects shows a properly of a standing wave, while the phase structure for the rest of subjects belongs to a traveling wave. Such phase properties agree with those of the spontaneous alpha waves for most of the subjects. Under the condition of the stimulus frequency higher than the alpha wave range, the SSVEP is similar to the traveling wave for most of the subjects. These results suggest that the spatial phase structure of the SSVEP is significantly affected by the alpha wave.